Attentional asymmetry between visual hemifields is related to habitual direction of reading and its implications for debate on cause and effects of dyslexia. (7th December 2017) - Kermani, Mojtaba; Verghese, Ashika; Vidyasagar, Trichur R.
Abstract : A major controversy regarding dyslexia is whether any of the many visual and phonological deficits found to be correlated with reading difficulty cause the impairment or result from the reduced amount of reading done by dyslexics. We studied this question by comparing a visual capacity in the left and right visual hemifields in people habitually reading scripts written right‐to‐left or left‐to‐right. Selective visual attention is necessary for efficient visual search and also for the sequential recognition of letters in words. Because such attentional allocation during reading depends on the direction in which one is reading, asymmetries in search efficiency may reflect biases arising from the habitual direction of reading. We studied this by examining search performance in three cohorts: (a) left‐to‐right readers who read English fluently; (b) right‐to‐left readers fluent in reading Farsi but not any left‐to‐right script; and (c) bilingual readers fluent in English and in Farsi, Arabic, or Hebrew. Left‐to‐right readers showed better search performance in the right hemifield and right‐to‐left readers in the left hemifield, but bilingual readers showed no such asymmetries. Thus, reading experience biases search performance in the direction of reading, which has implications for the cause and effect relationships between reading and cognitive functions.